Toxicity of smelter slag‐contaminated sediments from Upper Lake Roosevelt and associated metals to early life stage White Sturgeon (Acipenser transmontanus Richardson, 1836). (4th September 2014) - Little, E. E.; Calfee, R. D.; Linder, G.
Summary The toxicity of five smelter slag‐contaminated sediments from the upper Columbia River and metals associated with those slags (cadmium, copper, zinc) was evaluated in 96‐h exposures of White Sturgeon (Acipenser transmontanus Richardson, 1836) at 8 and 30 days post‐hatch. Leachates prepared from slag‐contaminated sediments were evaluated for toxicity. Leachates yielded a maximum aqueous copper concentration of 11.8 μg L−1 observed in sediment collected at Dead Man's Eddy (DME), the sampling site nearest the smelter. All leachates were nonlethal to sturgeon that were 8 day post‐hatch (dph), but leachates from three of the five sediments were toxic to fish that were 30 dph, suggesting that the latter life stage is highly vulnerable to metals exposure. Fish maintained consistent and prolonged contact with sediments and did not avoid contaminated sediments when provided a choice between contaminated and uncontaminated sediments. White Sturgeon also failed to avoid aqueous copper (1.5–20 μg L−1). In water‐only 96‐h exposures of 35 dph sturgeon with the three metals, similar toxicity was observed during exposure to water spiked with copper alone and in combination with cadmium and zinc. Cadmium ranging from 3.2 to 41 μg L−1 or zinc ranging from 21 to 275 μg L−1 was not lethal, but induced adverse behavioral changes including a loss of equilibrium. These results suggest that metals associated with smelter slags may pose an increased exposure risk to early life stage sturgeon if fish occupy areas contaminated by slags.